The Relationship between Premenopausal Syndrome and Stress Levels in Women in Lubuk Buaya Subdistrict, Padang City - Nadhiati Awlia Nasution; Lidwina Trieleventa Lumruan Sihombing (JURNAL KEBIDANAN KESTRA (JKK), 2026)
Background: Premenopause is characterised by a decline in ovarian oestrogen levels, which can cause physical and psychological complaints known as premenopausal syndrome. Various factors can trigger stress in premenopausal women, one of which is the changes caused by premenopausal syndrome. Objective: The objective of this study was to determine the relationship between premenopausal syndrome and stress levels in premenopausal women in Lubuk Buaya Village, Koto Tangah District, Padang City. Method: This was a quantitative study with a cross-sectional design. The sample in this study consisted of 80 premenopausal women who had not yet experienced menopause and resided in Lubuk Buaya Village. Data collection was conducted through observation and questionnaires. Data analysis was performed using linear regression analysis. Results: The results showed that 45% of the participants experienced mild symptoms of premenopausal syndrome and 46.3% experienced mild stress levels. The results of the linear regression analysis showed that the calculated r was greater than the table r (0.594 > 0.220). This indicates that premenopausal syndrome has a significant relationship with stress levels, accounting for 35.3%, while the remaining 64.7% is determined by other factors.